A longer-run perspective on fiscal sustainability - Afonso, António (2014)
We investigate the sustainability of fiscal policy in a set of 19 countries by taking a longer-run secular perspective over the period 1880–2009. Via a systematic analysis of the stationarity of the first-differenced level of government debt, and disentangling the components of the debt series using structural time series models, we conclude that since in most cases non-stationarity can be rejected, longer-run fiscal sustainability is not rejected (Japan and Spain can be exceptions). The same is true for a panel analysis when allowing for multiple structural breaks, and for cross-country dependence. In addition, endogenously identified breaks can be related to episodes of sovereign default.